Exploration of Antioxidant, Anti-inflammatory and Anticancer Potential of Substituted 4-Thiazolidinone Derivatives: Synthesis, Biological Evaluation and Docking Studies - Archna; Chawla P.A.; Teli G.; Pathania S.; Singh S.; Srivastava V. (My University, 2025)
Heterocyclic scaffolds are playing the important role in drug discovery and development. Currently many heterocyclic scaffolds like thiazole, thiazolidinone or thiazolidinedione have proved to be vital or provide life support against cancer and inflammation. The present work reports the ten 4-thiazolidinone derivatives synthesized via conventional route using three subsequent steps. The structural identification of the compounds was determined through spectrophotometric analysis. Further, the synthesized compounds were subjected to antioxidant, anti-inflammatory, and anticancer activities. All the synthesized derivatives possessed good to moderate antioxidant effects with maximum scavenging exhibited by FP7 and FP10. The in vivo anti-inflammatory activity was performed by the carrageenan-induced rat paw edema method and the compounds FP4 and FP7 possessed maximum inhibition. The synthesized analogs were subjected to in vitro antitumor activity over MOLT-4, EAC cell lines and it was found that compounds FP4, FP7, and FP10 emerged out as the most potent analogs against the tested cell lines. Molecular docking studies were carried out using Auto Dock 4.2.6 software. Structure-activity relationship gave a clear picture of title compounds such as electron-donating (OH, OCH3) groups at arylidene ring at position-5 increase antioxidant activity and is decreased by the presence of an electron-withdrawing group at the same position. Chloro substituted phenyl imino group at second position enhanced the anti-inflammatory activity while substituting electron-donating groups on arylidene moiety attached with fifth position of 4-thiazolidinone improved the anticancer activity. © 2022 Taylor & Francis Group, LLC.